Conceptual operation strategies of artificial intelligence metaphors in Indonesian mass media: A cognitive linguistic study - Mansyur, Umar; Jufri (LITERA, 2025)
This study aims to analyze the conceptual operation strategy of artificial intelligence (AI) metaphors in Indonesian mass media using cognitive linguistic studies. This research uses a qualitative approach with Christopher Hart’s Cognitive Linguistic–Critical Discourse Studies (CL-CDS) analysis method. Data sources came from online mass media articles that have a major influence on public opinion in Indonesia. Data were collected using documentation study techniques and analyzed using four CL-CDS strategies, namely structural configuration, framing, identification, and positioning. The results indicate that AI metaphors in mass media not only frame the way humans perceive AI capabilities and functions but also reflect the ideology and power behind current technological developments. This demonstrates the use of technological ideologies to support an agenda that enlarges society’s dependence on technological systems controlled by large corporations or the state while reinforcing existing power structures. This research contributes to providing insights for media practitioners, policymakers, and academics on the effective use of metaphors in conveying information about AI while considering its ideological and social impacts. Future research recommendations include analyzing the role of social media in framing AI, as well as investigating the ethics and social impact of AI discourse in the mass media.